2019
DOI: 10.1007/s10869-019-09629-8
|View full text |Cite
|
Sign up to set email alerts
|

FSSBs and Elderly Care: Exploring the Role of Organizational Context on Employees’ Overall Health and Work–Family Balance Satisfaction

Abstract: Fierce competition coupled with an increasing presence of dual-earning couples and blurred boundaries between work and family, increasingly render work-family lives of employees important. In this context, one strategy to enable employees achieve greater work-family interface is via Family Supportive Supervisor Behaviors (FSSBs), defined as supervisors' informal discretion to implement family-friendly policies at work. Inspired by the growth in research on FSSBs, the over-arching goal of this study is to explo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 118 publications
2
32
0
Order By: Relevance
“…FSSB constitutes a key factor for employees to achieve WLB and thus impacts organizational and individual outcomes (Idrovo & Bosch, 2019). Therefore, FSSB makes it easier for workers to cultivate a better work-family interface and, consequently, an adequate WLB (Rofcanin et al, 2020). Consequently, with the findings of the relationships between FSSB and WLB, on the one hand, and job performance, it was also found that WLB exerts a mediating effect on the relationship between FSSB and job performance.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…FSSB constitutes a key factor for employees to achieve WLB and thus impacts organizational and individual outcomes (Idrovo & Bosch, 2019). Therefore, FSSB makes it easier for workers to cultivate a better work-family interface and, consequently, an adequate WLB (Rofcanin et al, 2020). Consequently, with the findings of the relationships between FSSB and WLB, on the one hand, and job performance, it was also found that WLB exerts a mediating effect on the relationship between FSSB and job performance.…”
Section: Discussionmentioning
confidence: 95%
“…In organizations that offer benefits for their employees to improve WLB, supervisor support is very important, as it promotes their employees' perception that the supervisor recognizes their efforts and cares about their well-being (Talukder et al, 2018). Recent research reaffirms that there is a positive relationship between FSSB and satisfaction with work-family balance (Idrovo & Bosch, 2019;Rofcanin et al, 2020). FSSB increases employees' energy, enthusiasm and positive mood at work (Straub et al, 2019).…”
Section: Family Supportive Supervisor Behaviour and Work-life Balancementioning
confidence: 99%
“…We account for the role of family‐supportive environments by considering the individual perceptions of the extent to which an organisation is characterised by work family‐friendly culture (WFFC; Rofcanin, Heras, Escibano, & Stanko, 2019; Valcour, Ollier‐Malaterre, Matz‐Costa, Pitt‐Catsouphes, & Brown, 2011). Perceptions of WFFC include two elements: demonstrating career support and enabling employees to work with flexible work schedules.…”
Section: Introductionmentioning
confidence: 99%
“…However, research on both topics has been mainly carried out in developed Northern Europe countries and the English speaking world. Researchers have studied different aspects related to family‐friendly companies in some Southern European and Latin American countries (e.g., Adame, Caplliure, & Miquel, 2016; Bosch et al, 2018; Las Heras, Van der Heijden, De Jong, & Rofcanin, 2017; Poelmans, Chinchilla, & Cardona, 2003; Rofcanin, Las Heras, Escribano, & Stanko, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study, Rofcanin et al (2020) explored the role of organizational context on employees' overall health and work–family balance satisfaction using data of 822 subordinates and 346 supervisors collected in a financial services company in El Salvador and one retail company in Perú. Results using multilevel analysis underline the importance of supervisor support in promoting family‐supportive supervisory behaviors, employee perceptions of health and work–family balance satisfaction.…”
Section: Introductionmentioning
confidence: 99%